Effect of clay materials on phase separation in plastic bag waste-modified bitumen during high-temperature storage - Mohammed Nouali; Zohra Derriche; Elhem Ghorbel (Transportation Engineering)
Phase separation at high storage temperatures is a significant challenge in the practical application of polymer-modified bitumen (PmB), as it impacts negatively the uniformity and stability of modified binders. This study evaluates the effects of montmorillonite (MMT) and kaolinite clay (KC) additions on phase separation in a High-density polyethylene (HDPE) plastic waste-modified bitumen. Clay minerals are widely studied as compatibilizing agents, that prevent binder phase separation in bitumen/polymer/clay blends as often evaluated through softening point testing. In addition to conventional physical and rheological evaluations, the apparent molecular weight distribution (AMWD) and a new bitumen dissolution test are proposed in this study for the first time to analyze phase separation in bitumen/plastic/clay ternary blends. Results indicate that while clay addition reduces phase separation potential of PmB as indicated by both softening point measurements and rheological derived phase separation indices, AMWD and dissolution test reveal significant phase separation occurs equally in both WP and WP/clay binders. Phase separation phenomenon occurs probably because Van der Waals forces between clay particles are insufficient to counteract the effect of plastic particle coalescence driving forces. As a result of phase separation, plastic particles migrate upward (creaming) and coalesce, while clay particles settle down at the bottom of the binder specimen. These findings demonstrate the limitations of consistency difference and rheological indices when used for evaluating phase separation in ternary blends. The AMWD and dissolution results offer more reliable evaluation methods for assessing phase separation in PmB.